Můj neznámý vojín - Kryvenko, Anna (Czech Republic ; Latvia ; Slovakia : Analog Vision, 2018)
By weaving together rare archival footage from Europe and Russia with her own family history, Anna Kryvenko offers an unusual perspective on the 1968 occupation of Czechoslovakia. While visiting her family home, Anna discovers a photo album full of pictures with one person cut out of the photos—her great-grand-uncle, a man who unwillingly became part of the occupation of Czechoslovakia in 1968 as a Soviet soldier. While trying to piece together his story, she touches upon some very current topics: the fragmentation of personal vs. national memory, inherited guilt, historical interpretation, media manipulation, Europe’s relationship with Russia, and also, the attitude of Czechs and Slovaks towards foreigners.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films